2015
DOI: 10.1002/eqe.2561
|View full text |Cite
|
Sign up to set email alerts
|

Damage response of multistorey r/c buildings with different structural systems subjected to seismic motion of arbitrary orientation

Abstract: SUMMARYIn the present study the combined influence of seismic orientation and a number of parameters characterizing the structural system of Reinforced Concrete (R/C) buildings on the level of expected damages are examined. For the purposes of the above investigation eight medium-rise buildings are designed on the basis of the current seismic codes. The structural characteristics examined are the ratio of the base shear received by the structural walls, the ratio of horizontal stiffness in two orthogonal direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Some recent researches have shown that the maximum ductility demand of an elastoplastic single-degree-of-freedom system could occur at a different angle from the as-recorded one [Garcia-Soto, Hong, and Gómez, 2012]. Similar conclusions have been observed when estimating the maximum displacement response and maximum expected damage of 3D multi-degree-of-freedom building models [Kostinakis et al, 2015;Kostinakis et al, 2018;Vargas-Alzate et al, 2018]. To analyze this effect for a particular building and earthquake, by considering the CRM, the following steps should be achieved:…”
Section: Complete Rotational Methodsmentioning
confidence: 71%
“…Some recent researches have shown that the maximum ductility demand of an elastoplastic single-degree-of-freedom system could occur at a different angle from the as-recorded one [Garcia-Soto, Hong, and Gómez, 2012]. Similar conclusions have been observed when estimating the maximum displacement response and maximum expected damage of 3D multi-degree-of-freedom building models [Kostinakis et al, 2015;Kostinakis et al, 2018;Vargas-Alzate et al, 2018]. To analyze this effect for a particular building and earthquake, by considering the CRM, the following steps should be achieved:…”
Section: Complete Rotational Methodsmentioning
confidence: 71%
“…Magliulo et al, based on 3 multistory reinforced concrete (RC) buildings and using both roof displacements and plastic hinge rotations as Engineering Demand Parameters (EDPs), showed that there is an increase of up to 37% for rotated records. Kostinakis et al studied 8 mid‐rise RC buildings of various structural systems and found the damage level to be strongly affected by the orientation to a degree that is a function of the structural system, the eccentricity, and the distance of the record to the fault rupture. Nievas and Sullivan highlighted the different levels of orientation influence with respect to structural typology, while Taskari and Sextos proposed the derivation of multiangle fragility curve for bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the critical angle for a given response quantity depends on fundamental period, model type and level of inelastic behavior and it is difficult to be determined a priori, as in case of elastic structures. In a series of research studies conducted by Kostinakis et al [4][5][6][7] and Fontara et al [8] the influence of the seismic motion's orientation on the elastic and inelastic seismic behaviour of RC structures was investigated. They found that the structural response is strongly dependent on the strong motion's direction.…”
Section: Introductionmentioning
confidence: 99%